USING INTERACTIVE METHODS IN TEACHING GRAMMAR - Farmanova Malika Axrorovna.; Qurbonova Sitora Ilxom qizi; Qurbonova Shohsanam Negmatulla qizi (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, several methods of effectively teaching English to children and some of the modern technologies used in the learning process are highlighted.